Physicochemical properties of different thickeners used in infant foods and their relationship with mineral availability during in vitro digestion process. (December 2015) - González-Bermúdez, Carlos Alberto; Castro, Alejandra; Perez-Rea, Daysi; Frontela-Saseta, Carmen; Martínez-Graciá, Carmen; Nilsson, Lars
Abstract: Locust bean gum (LBG) and modified starches are commonly used as thickeners in food products for infants. However, there is no consensus on their possible effects on infant nutrition, especially on mineral availability. The aim of the present work was to characterize the effect of LBG, cross-linked, hydroxypropylated maize starch (Mhdp) and pre-gelatinized rice starch (gRS) on Ca, Fe and Zn availability during a gastric and intestinal in vitro digestion assay in relation to their physicochemical properties in solution (apparent viscosity, solubility, molar mass (M) and conformational properties) through the simulated digestion process. LBG gave the highest decrease in Ca and Fe gastric (17.96% and 17.6% respectively) and intestinal (19.5% and 13.5%) solubility with respect to the reference without thickeners. Ca (11.1% ± 1.1), Fe (2.77% ± 0.3) and Zn (7.78% ± 0.6) dialyzability was also lower than for the reference (23.4% ± 2.9; 19.65% ± 3.53 and 27.74% ± 3.3 respectively). LBG solubility remained stable during gastric digestion, decreasing significantly from a range of 65–69% to 61.1% after intestinal digestion. LBG viscosity remained stable during the digestion process, being these findings attributable to its resistance to enzymes. On the other hand, the addition to Mhdp or gRS slightly affected Ca and Fe solubility or Ca dialyzability, decreasing after gastric digestion and then increasing after intestinal digestion with respect to the reference. These results correlated to the changes in their viscosity enhancing properties, which increased during gastric digestion and decreased after intestinal digestion, being attributable to their digestion by pancreatic enzymes. Gastric digestion resulted in an increase in M for the modified starches (more pronounced for gRS). The increase in mineral solubility and dialyzability after intestinal digestion with respect to the gastric stage was explained by the degradation of starches by intestinal enzymes, which resulted in a decrease in apparent shear viscosity (from 1.2 to 1 Pa s, measured in a shear rate range 0.00–50 s − 1 ) and an increase in solubility (from 3 to 6% to approximately 70%) after intestinal digestion. In conclusion, LBG could be more effective than Mhdp and gRS as thickener, providing higher viscosity and resistance to digestive process. However, its negative effect on mineral solubility and dialyzability should be taken into account. On the contrary, Mhdp and gRS showed to be degraded after intestinal digestion. Highlights: Thickeners used in infant food industry Physicochemical properties of thickeners Locust bean gum remains stable during the digestion process. Starches do not negatively affect mineral availability.